Modern Imagology: Significance and Development Prospects - M. D. Bakhareva (Концепт: философия, религия, культура, 2022)
With the revival of nationalism and identity politics, imagological studies that analyze attitudes, stereotypes and prejudices about one’s own and others’ national character are becoming increasingly relevant. These studies investigate relationships that govern rhetoric, discursive representation, literary activity, and ultimately international relations in general. Imagology is currently intensively developing in literary criticism and other humanities, which also determines the relevance of this study. The purpose of this review article is to analyze scientific publications on the theoretical and practical aspects of imagology over the past 10 years in order to determine its significance and development prospects in the era of globalization. Тhe object of the study is the significance and prospects for the development of imagology; the subject of the study are scientific publications on imagological topics over the past 10 years. The choice of sources for this review was made by the keyword imagology on the following resources: Scopus, Cyberleninka, as well as Imagologica.eu — a site dedicated to imagological research over the past 10 years. An analysis of the main specialized series and collections of articles on imagology was carried out in order to identify the predominant topics of publications and confirm the role of imagology in literary criticism and other humanities. The study of modern Russian and foreign publications on imagological topics has shown that the modern environment is open to studying the discursively constructed nature of many social and cultural values. Thus, a large number of publications on imagological topics testify to the importance of modern imagology, its great prospects and continuous development. The analysis showed the main directions of research in modern imagology and proved that at present imagology is not concerned with isolated images, but with their relationships and associative links with other images, chronological boundaries of the dispersion of images, and shifts in content elements. Combining various approaches of contextual analysis (socio-historical, ethno-psychological and cultural-political), makes the imagological method effective and universal. It must be emphasized that imagology takes on the political mission of deconstructing nationalist reasoning and thus contributes to a better understanding between peoples. In cross-cultural, transnational and globalization studies, imagology has the potential to break stereotypes that oppose nations to each other and to find ways to interact.